Pelatihan Penggunaan Aplikasi Canva dalam Pembuatan Media Pembelajaran Interaktif kepada Siswa Kelas XII MA Hidayatul Mubtadi’in - Iko, Iko; Riyanto, Riyanto; Adi, Adi (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P2M) IKIP Budi Utomo Malang, 2024)
A Training in creating interactive learning media assisted by the Canva application which was carried out in the Potential Based Community Service (PMBP) program which is one of the activities important for the Academic Community as academic functional staff both for develop knowledge and solve problems. Devotion to This society aims to provide education to the public regarding development and management of resources, especially in media training Canva based learning, Activities Doing this will certainly have an impact on the school. Where the results can be obtained, namely increasing the results of creativity can create a simple Canva-based learning media product, the results obtained from this training in making learning media will be a provision for students after completing their education. The research results show that the use of the Canva application in the process of creating interactive learning media becomes an interesting and creative learning media development of 21st century schooling, especially in all areas of use innovation in everyday life. Thus, the final conclusion in writing This article explains that the Canva application is very easy and practical to access in learning activities. Application of the Canva application in interactive learning media is the right solution to help educators in creating media computerized learning in the 21st century so that the delivery of material learning can be more easily accepted by students.